Decorative film
By using a polyester resin adhesive layer with low initial adhesive strength but increasing over time, the peeling problem of the decorative film when foreign matter is mixed and the problem of insufficient water resistance is solved, and the effect of easy peeling and excellent water resistance is achieved.
Patent Information
- Application Number
- CN202480008233.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-31
- Filing Date
- 2024-01-09
- Publication Date
- 2025-09-05
AI Technical Summary
The existing decorative film is difficult to easily peel off from the adhesive body when foreign matter is mixed, and has insufficient water resistance, resulting in appearance damage and material utilization.
Using a polyester resin adhesive layer with low initial adhesive strength but increasing over time, by controlling the adhesive strength ratio and viscoelastic parameters, it is ensured that the decorative film can be easily peeled off when foreign matter is mixed and maintains the adhesive strength stable for a long time.
The decorative film can be easily peeled off after foreign matter is mixed and not easily detached from the adhered body, and has excellent water resistance to avoid appearance damage and material waste.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] One embodiment of the present invention relates to a decorative film. Background Art
[0002] When attaching decorative films with adhesive layers to adhered objects through vacuum forming or vacuum compressed air forming, foreign matter such as dust can enter between the adherend and the adhesive layer of the decorative film, causing uneven surfaces and impaired appearance. In the event of foreign matter, the decorative film must be peeled off from the adherend and a new film applied. However, this requires significant force, which can easily result in adhesive residue and reduce raw material utilization. Furthermore, when using decorative films for vehicle exterior applications, water resistance during car washes and other conditions can be a concern.
[0003] For example, Patent Document 1 discloses a decorative film made of acrylic resin, and states that when the decorative film is attached using a vacuum compressed air forming method, it can mask the intrusion of foreign matter such as dust and the unevenness of the adherend surface. Prior art literature Patent Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2017-119403 Summary of the Invention Technical problem to be solved by the invention
[0005] One of the objects of the present invention is to provide a decorative film that can be easily peeled off immediately after application even when foreign matter is mixed in, is unlikely to peel off or float off the adherend due to increased adhesive strength over a long period of time, and has excellent water resistance. Technical solutions used to solve technical problems
[0006] The present inventors conducted intensive research and found that the above-mentioned problems can be solved by using a decorative film provided with a pressure-sensitive adhesive layer having low initial adhesive strength immediately after attachment to an adherend and whose adhesive strength increases with time, thereby completing the present invention.
[0007] The present invention relates to, for example, the following [1] to [6]. [1] A decorative film comprising a substrate and an adhesive layer formed from an adhesive composition containing a polyester resin (A), wherein: The ratio (b / a) of the adhesive strength (a) to the adhesive strength (b) of the adhesive layer measured by the following adhesion test is greater than 1.5; The storage modulus (G') of the adhesive layer measured by a dynamic viscoelasticity test at 23°C and 1 Hz is 1.0×10 4 Pa and above 1.0×107 Pa below; and The adhesive layer has a loss tangent value (tan δ) of 0.5 or more and 10.0 or less when measured by a dynamic viscoelasticity test at 23° C. and 0.01 Hz; [Adhesion test] Adhesion (a): A 150 mm x 20 mm test piece was cut from an adhesive sheet for adhesion testing consisting of a 20 μm thick adhesive layer and a 50 μm thick easily moldable polyethylene terephthalate sheet located on one side of the adhesive layer. The adhesive layer was affixed to a polycarbonate plate. The plate was left in an environment of 23°C and 50% RH for 30 seconds, and then the 180-degree peel strength (N / 20 mm) at a peel speed of 300 mm / min was measured using a tensile testing machine to obtain the adhesion. Adhesion (b): A 150 mm x 20 mm test piece was cut from the adhesive sheet used for the adhesion test. The adhesive layer was attached to a polycarbonate plate. The plate was left in an environment of 23°C and 50% RH for 20 minutes. The 180-degree peel strength (N / 20 mm) at a peel speed of 300 mm / min was then measured using a tensile tester to determine the adhesion.
[0008] [2] The decorative film according to [1], wherein the adhesive force (a) is greater than 0.8 N / 20 mm and not more than 7.0 N / 20 mm.
[0009] [3] The decorative film according to [1] or [2], wherein the adhesive composition contains less than 4 parts by mass of the curing agent (B) based on 100 parts by mass of the polyester resin (A).
[0010] [4] The decorative film according to any one of [1] to [3], wherein the polyester resin (A) is a polyester emulsion.
[0011] [5] The decorative film according to any one of [1] to [3], wherein the polyester resin (A) is a self-emulsifiable resin.
[0012] [6] The decorative film described in [4], wherein the polyester emulsion is at least one emulsion selected from an emulsion obtained by dispersing a polyester resin having a sulfonic acid group in an aqueous medium and an emulsion obtained by neutralizing a polyester resin having a carboxyl group with an alkaline compound and dispersing the same in an aqueous medium. Effects of the Invention
[0013] The decorative film according to one embodiment of the present invention can be easily peeled off immediately after application even when foreign matter is mixed in, is unlikely to peel or float from the adherend due to increased adhesive strength over a long period of time, and has excellent water resistance. DETAILED DESCRIPTION
[0014] Hereinafter, the present invention will be described in detail. In the present invention, unless otherwise specified, A to B indicating a numerical range means A or more and B or less.
[0015] [Decorative film] A decorative film according to one embodiment of the present invention is a decorative film comprising a substrate and an adhesive layer formed from an adhesive composition containing a polyester resin, wherein: The ratio (b / a) of the adhesive strength (a) to the adhesive strength (b) of the adhesive layer measured by the following adhesion test is greater than 1.5; The storage modulus (G') of the adhesive layer measured by a dynamic viscoelasticity test at 23°C and 1 Hz is 1.0×10 4 Pa and above 1.0×10 7 Pa below; and The pressure-sensitive adhesive layer has a loss tangent value (tan δ) of 0.5 or more and 10.0 or less when measured by a dynamic viscoelasticity test at 23° C. and 0.01 Hz. [Adhesion test] Adhesion (a): A 150 mm x 20 mm test piece was cut from an adhesive sheet for adhesion testing consisting of a 20 μm thick adhesive layer and a 50 μm thick easily moldable polyethylene terephthalate sheet located on one side of the adhesive layer. The adhesive layer was affixed to a polycarbonate plate. The plate was left in an environment of 23°C and 50% RH for 30 seconds, and then the 180-degree peel strength (N / 20 mm) at a peel speed of 300 mm / min was measured using a tensile testing machine to obtain the adhesion. Adhesion (b): A 150 mm x 20 mm test piece was cut from the adhesive sheet used for the adhesion test. The adhesive layer was attached to a polycarbonate plate. The plate was left in an environment of 23°C and 50% RH for 20 minutes. The 180-degree peel strength (N / 20 mm) at a peel speed of 300 mm / min was then measured using a tensile tester to determine the adhesion.
[0016] The decorative film according to one embodiment of the present invention utilizes an adhesive layer with a predetermined adhesive strength to the adherend. This allows for easy peeling immediately after application, even in the presence of foreign matter. It is also less susceptible to peeling or lifting from the adherend over time due to increased adhesive strength, and exhibits excellent water resistance. Furthermore, the adhesive layer possesses a predetermined viscoelasticity (storage modulus and loss tangent), enabling it to exhibit appropriate adhesive strength.
[0017] In the decorative film of one embodiment of the present invention, the base material preferably plays a decorative role, but a decorative layer may also be provided. In addition, the decorative film of one embodiment of the present invention may also have a release film on the adhesive layer to protect the adhesive layer before use.
[0018] [Base material] The decorative film according to one embodiment of the present invention includes a base material. The base material generally constitutes the outermost layer of a decorative molded body obtained by attaching the decorative film to an adherend to be decorated. The substrate may be colored or colorless, and may be transparent, translucent, or opaque.
[0019] The substrate is preferably in the form of a film or sheet, and may be a single-layer structure or may be composed of multiple layers. The thickness of the substrate is preferably 10 to 1000 μm, more preferably 20 to 500 μm, and even more preferably 50 to 300 μm.
[0020] Examples of the substrate include those formed from thermoplastic resins. The thermoplastic resin is preferably composed of at least one selected from polyvinyl chloride, polyethylene terephthalate, polymethyl methacrylate, polycarbonate, acrylonitrile butadiene styrene (ABS) resin, polyurethane, polyethylene, and polypropylene. Among these, at least one selected from polyvinyl chloride, polyethylene terephthalate, polymethyl methacrylate, polycarbonate, and ABS resin is more preferred, with polyethylene terephthalate being particularly preferred. In the case of polyethylene terephthalate (PET), in addition to conventional crystalline PET, there are also amorphous PET known as A-PET and PETG. PET, which has been given moldability and is known as easy-to-mold PET, is particularly preferred.
[0021] The Young's modulus of the substrate at 23°C measured according to JIS K 7127 (1999) is preferably 40 N / mm 2 More than 600N / mm 2 Above, more preferably at 900N / mm 2 If the Young's modulus is 40N / mm 2 The above, the obtained decorative film is not easily deformed, so the concavo-convex shape provided on the adhesive layer is not easily presented on the surface, and it is not easy to cause problems in appearance. On the other hand, the upper limit of the Young's modulus is preferably 8000N / mm 2 Below, more preferably 6500N / mm 2 Below, further preferably at 3000N / mm 2 If the Young's modulus is 8000N / mm 2 These upper and lower limits can be combined arbitrarily.
[0022] In addition, depending on the application, the substrate may also contain inorganic particles such as silicon dioxide, plasticizers, colorants, ultraviolet absorbers and other substances that impart functionality. In addition, patterns, characters, and designs for imparting design properties may be printed on the surface of the substrate, or patterns, characters, and designs may be formed inside the substrate.
[0023] [Adhesive layer] The decorative film according to one embodiment of the present invention includes an adhesive layer formed from an adhesive composition containing a polyester resin (A).
[0024] Adhesion of adhesive layer to polycarbonate sheet The adhesive strength of the adhesive layer to the polycarbonate plate can be measured by the following method, the details of which are described in the Examples below. From the adhesive force test consisting of the described adhesive layer of thickness 20 μm and the easy-to-form polyethylene terephthalate of thickness 50 μm on one side of the adhesive layer, cut out a test piece of 150mm × 20mm with an adhesive sheet, the described adhesive layer is pasted on the polycarbonate plate adherend, after being placed for 30 seconds under 23 ℃, 50%RH environment, the 180 degree peel strength (N / 20mm) under the peeling speed 300mm / min is measured with a tensile testing machine, whereby adhesive force (a) can be achieved. By changing the standing time after being pasted on the above-mentioned adherend in the condition of achieving the above-mentioned adhesive force (a), the adhesive force (b) after 20 minutes can be achieved. And then, the adhesive force after 24 hours can also be achieved by the same method, and the adhesive force after 24 hours will be recorded as adhesive force (c) below. As a tensile testing machine, for example, Autograph (" Autograph AG-X " made by Shimadzu Corporation) can be used.
[0025] In the adhesive layer, the ratio (b / a) of the adhesive strength (a) to the adhesive strength (b), as measured by the above method, is 1.5 or greater, preferably 2 to 1000, and more preferably 3 to 100. When b / a is 1.5 or greater, the initial adhesive strength between the adhesive layer and the adherend is sufficiently low, thereby tending to facilitate the production of the desired decorative film that can be easily peeled from the adherend immediately after application, even in the presence of foreign matter.
[0026] In the adhesive layer, the ratio (c / a) of the adhesive strength (a) to the adhesive strength (c) measured by the above method is preferably 3.5 or greater, more preferably 8 to 1000, and even more preferably 9 to 100. When c / a is 3.5 or greater, the decorative film is less likely to peel off or float from the adherend due to an increase in adhesive strength over time, and the desired decorative film tends to be easily obtained.
[0027] The adhesive strength (a) of the adhesive layer after 30 seconds, as measured by the above method, is preferably greater than 0.8 N / 20 mm and less than 7.0 N / 20 mm, more preferably greater than 0.9 N / 20 mm and less than 6.0 N / 20 mm, and even more preferably greater than 0.9 N / 20 mm and less than 5.0 N / 20 mm. When the adhesive strength (a) is within the above range, the initial adhesion between the adhesive layer and the adherend is sufficiently low, thereby facilitating the production of a desired decorative film that can be easily removed immediately after application, even in the presence of foreign matter.
[0028] In the adhesive layer, the adhesive strength (b) after 20 minutes measured by the above method is preferably 3.0 N / 20 mm or more and 15.0 N / 20 mm or less, more preferably 3.5 N / 20 mm or more and 14.0 N / 20 mm or less, and further preferably 3.5 N / 20 mm or more and 13.0 N / 20 mm or less.
[0029] The adhesive strength (c) of the adhesive layer after 24 hours, as measured by the above method, is preferably 10.0 N / 20 mm or more and 30.0 N / 20 mm or less, more preferably 11.0 N / 20 mm or more and 20.0 N / 20 mm or less, and even more preferably 11.0 N / 20 mm or more and 18.0 N / 20 mm or less. When the adhesive strength (c) is within this range, the decorative film is less likely to peel off or float from the adherend over an extended period of time.
[0030] The adhesive force of the adhesive layer to an acrylonitrile-butadiene-styrene plate can be measured by the following method in addition to the adhesive force to the polycarbonate plate.
[0031] Adhesion of adhesive layer to acrylonitrile butadiene styrene board The adhesive strength of the adhesive layer to an acrylonitrile butadiene styrene plate was measured under the same conditions as described above in the "Adhesion Strength of the Adhesive Layer to a Polycarbonate Plate" column, except that the adherend was replaced with an acrylonitrile butadiene styrene plate. Details are described in the Examples below. The adhesive strengths measured by this method were recorded as the adhesive strength after 30 seconds (d), the adhesive strength after 20 minutes (e), and the adhesive strength after 24 hours (f).
[0032] In the adhesive layer, the ratio (e / d) of the adhesive strength (d) to the adhesive strength (e) measured by the above method is preferably 1.5 or greater, more preferably 2 to 1000, and even more preferably 3 to 100. When e / d is 1.5 or greater, the initial adhesive strength between the adhesive layer and the adherend is sufficiently low, thereby tending to facilitate the production of the desired decorative film that can be easily peeled from the adherend immediately after application, even in the presence of foreign matter.
[0033] The preferred range of the ratio (f / d) of the adhesive force (d) to the adhesive force (f) is the same as the preferred range of the ratio (c / a) of the adhesive force (a) to the adhesive force (c) described in the above "Adhesion of the adhesive layer to the polycarbonate plate" column.
[0034] The preferred ranges of adhesion (d), adhesion (e) and adhesion (f) are respectively the same as the preferred ranges of adhesion (a), adhesion (b) and adhesion (c) described in the above “Adhesion of adhesive layer to polycarbonate plate” column.
[0035] (Adhesive Sheet) The adhesive sheet includes the adhesive layer and a release film provided on one or both sides of the adhesive layer. The details of the method for preparing the adhesive sheet are described in the examples below. The pressure-sensitive adhesive sheet for an adhesive strength test according to one embodiment of the present invention comprises the pressure-sensitive adhesive layer having a thickness of 20 μm and a 50 μm easily moldable polyethylene terephthalate film located on one surface of the pressure-sensitive adhesive layer.
[0036] Storage modulus (G') The storage modulus (G') of the adhesive layer measured by the dynamic viscoelasticity test according to JIS K 7244 at 23°C and 1 Hz is 1.0×10 4 Pa and above 1.0×10 7 Pa or less, preferably 5.0×10 4 Pa and above 5.0×10 6 Pa or less, more preferably 1.0×10 5 Pa and above 9.5×10 5 Pa or less. When the storage modulus (G') is within this range, the initial adhesive strength is sufficiently low, allowing the decorative film to be easily peeled off immediately after application even if foreign matter is present. The storage modulus (G') can be determined by the method described in the Examples below.
[0037] Loss tangent (tanδ) The loss tangent (tan δ) of the adhesive layer, when measured at 23°C and 0.01 Hz in accordance with the dynamic viscoelasticity test of JIS K 7244, is 0.5 or more and 10.0 or less, preferably 0.7 or more and 7.0 or less, and more preferably 1.0 or more and 5.0 or less. If the loss tangent is within the above range, the adhesive strength increases sufficiently over time, and thus there is a tendency that peeling or floating from the adherend is less likely to occur over a long period of time. In addition, the loss tangent can be obtained by the method described in the Examples below.
[0038] The thickness of the adhesive layer is preferably 3 to 1000 μm, more preferably 5 to 500 μm.
[0039] <Adhesive composition containing polyester resin (A)> The adhesive layer is formed from an adhesive composition containing a polyester resin (A) as described below. The adhesive composition is a composition containing a polyester resin (A) and, if necessary, other components.
[0040] Polyester resin (A) The polyester resin (A) used in the present invention is obtained by copolymerizing a copolymerization component comprising a polycarboxylic acid (A1) and a polyol (A2) as constituent raw materials. From the perspective of the balance between initial adhesive strength and adhesive strength over time, the polyol (A2) preferably contains at least one of a polyether diol (A2-1) and an alkylene glycol (A2-2).
[0041] Polycarboxylic acids (A1) Examples of the polycarboxylic acid (A1) used in the present invention include dicarboxylic acids and trivalent or higher polycarboxylic acids. However, dicarboxylic acids are preferably used because they can stably produce polyester resins.
[0042] Examples of the dicarboxylic acids include aliphatic dicarboxylic acids such as malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, thiodipropionic acid, and diglycolic acid; Aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, benzylmalonic acid, biphenylcarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, and naphthalene dicarboxylic acid; Alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acids, 1,2-cyclohexanedicarboxylic acids, 1,3-cyclopentanedicarboxylic acids, 1,4-cyclohexanedicarboxylic acids, 2,5-norbornanedicarboxylic acids, and adamantanedicarboxylic acids; etc. Examples of the trivalent or higher carboxylic acids include trimellitic acids, pyromellitic acids, adamantanetricarboxylic acids, and trimesic acids. These polycarboxylic acids (A1) may be used alone or in combination of two or more.
[0043] Among the polycarboxylic acids (A1), aromatic polycarboxylic acids (A1-1) are preferably used from the viewpoint of imparting cohesive force, and terephthalic acids and isophthalic acids are particularly preferably used.
[0044] The content of the aromatic polycarboxylic acid (A1-1) is preferably 30 mol% or more, more preferably 50 to 90 mol%, and even more preferably 60 to 80 mol% relative to the total amount of the polycarboxylic acid (A1). When the content is within the above range, the adhesive strength tends to be sufficiently increased over time.
[0045] Moreover, among the polycarboxylic acids (A1), aliphatic polycarboxylic acids can also be used from the viewpoint of imparting a sticky feel, and examples thereof include sebacic acid and azelaic acid.
[0046] The content of the aliphatic polycarboxylic acid is preferably 50 mol% or less, more preferably 40 mol% or less, and even more preferably 30 mol% or less relative to the total amount of the polycarboxylic acid (A1). When the content is within the above range, the adhesive strength tends to be sufficiently increased over time.
[0047] In the present invention, from the perspective of adhesive properties, an aromatic polycarboxylic acid (A1-1) and an aliphatic polycarboxylic acid may be used in combination as the polycarboxylic acid (A1). The content ratio (molar ratio) of the aromatic polycarboxylic acid (A1-1) to the aliphatic polycarboxylic acid is preferably aromatic polycarboxylic acid (A1-1) / aliphatic polycarboxylic acid = 30 / 70 to 100 / 0, more preferably 50 / 50 to 100 / 0, and even more preferably 80 / 20 to 100 / 0.
[0048] In order to increase the number of branch points in the polyester resin (A), it is preferable to use a trivalent or higher polycarboxylic acid. Among them, trimellitic acid is more preferably used because it is relatively less likely to cause gelation.
[0049] The content of the trivalent or higher polycarboxylic acid is preferably 10 mol% or less, more preferably 0.1 to 5 mol%, relative to the total polycarboxylic acid (A1), from the perspective of improving the cohesive strength of the adhesive. When the content is within the above range, gelation tends to be less likely to occur during the production of the polyester resin (A).
[0050] The content of the polycarboxylic acid (A1) relative to the total polyester resin (A) is preferably 5% by mass or more, more preferably 20 to 60% by mass, and even more preferably 30 to 50% by mass. When the content is within the above range, the initial adhesive strength tends to be sufficiently low.
[0051] Polyol (A2) Examples of the polyol (A2) used in the present invention include diols and trivalent or higher polyols.
[0052] Examples of the diol include aliphatic diols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol. Alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spirodiol, tricyclodecanedimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Aromatic diols such as 4,4'-thiodiphenol, 4,4'-methylenediphenol, 4,4'-biphenol, catechol, resorcinol, hydroquinone, 2,5-naphthalenediol, p-xylenediol, and their ethylene oxide and propylene oxide adducts; etc.
[0053] Examples of the trivalent or higher polyol include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol and adamantanetriol. Other examples include polyether diols (A2-1) such as polytetramethylene ether glycol, polyethylene glycol and polypropylene glycol.
[0054] These polyols (A2) may be used alone or in combination of two or more.
[0055] In the present invention, among the polyols (A2), aliphatic diols such as ethylene glycol, diethylene glycol, 1,6-hexanediol, and 2,2-dimethyl-1,3-propanediol are preferred from the viewpoint of reducing initial adhesive strength.
[0056] Among the polyols (A2), it is preferred to further contain a polyether diol (A2-1) from the viewpoint of reducing the initial adhesive strength, and among them, polytetramethylene ether glycol is preferably used.
[0057] The content of the polyether diol (A2-1) in the polyol (A2) is preferably 10 to 99 mol%, more preferably 30 to 98 mol%, and even more preferably 51 to 97 mol% relative to the total amount of the polyol (A2). When the content is within this range, the initial adhesive strength tends to be sufficiently low.
[0058] In the present invention, the polyol (A2) preferably further contains an alkylene glycol (A2-2) from the viewpoint of ease of polymerization. Examples of the alkylene glycol (A2-2) include aliphatic diols such as ethylene glycol, 1,4-butanediol, 1,6-hexanediol, and 2,2-dimethyl-1,3-propanediol (neopentyl glycol). Among them, 1,6-hexanediol, ethylene glycol, and 2,2-dimethyl-1,3-propanediol are preferably used.
[0059] The lower limit of the content of the alkylene glycol (A2-2) is preferably 1 mol% or more, more preferably 10 mol% or more, further preferably 30 mol% or more, and particularly preferably 70 mol% or more, relative to the total amount of the polyol (A2). On the other hand, the upper limit of the content of the alkylene glycol (A2-2) is preferably 100 mol% or less, more preferably 95 mol% or less, further preferably 90 mol% or less, and particularly preferably 85 mol% or less, relative to the total amount of the polyol (A2). These upper and lower limits may be arbitrarily combined. When the content is within the above range, stable resin formation tends to be easily achieved, and the adhesive strength tends to be sufficiently increased over time.
[0060] In order to increase the number of branch points in the polyester resin (A), it is preferred to use a trivalent or higher polyol. Examples of such a trivalent or higher polyol include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerol, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.
[0061] The content of the trivalent or higher polyol is preferably 20 mol% or less, more preferably 0.1 to 10 mol%, and even more preferably 0.5 to 5.0 mol%, relative to the total amount of the polyol (A2). When the content is within the above range, the polyester resin (A) tends to be easily produced.
[0062] The content of the polyol (A2) relative to the total polyester resin (A) is preferably 15% by mass or more, more preferably 40 to 95% by mass, and even more preferably 50 to 80% by mass. When the content is within the above range, the initial adhesive strength tends to be sufficiently low.
[0063] The blending ratio of the polycarboxylic acid (A1) to the polyol (A2) is preferably 1 to 3.0 equivalents, particularly preferably 1.1 to 2.0 equivalents, per 1 equivalent of the polycarboxylic acid (A1). When the blending ratio of the polyol (A2) is within the above range, the acid value is within an appropriate range, the molecular weight is easily increased, and the yield tends to be good.
[0064] (Method for producing polyester resin (A)) The polyester resin (A) used in the present invention can be produced by arbitrarily selecting the above-mentioned polycarboxylic acids (A1) and polyols (A2) and subjecting them to a polycondensation reaction in the presence of a catalyst by a known method.
[0065] During the polycondensation reaction, the esterification reaction is carried out first, and then the polycondensation reaction is carried out.
[0066] The catalyst used in the esterification reaction specifically includes titanium catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony catalysts such as antimony trioxide, germanium catalysts such as germanium dioxide, and catalysts such as zinc acetate, manganese acetate, and dibutyltin oxide. One or more of these catalysts can be used. Among them, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferred from the perspective of a balance between high catalytic activity and color.
[0067] The amount of the catalyst added is preferably 1 to 10,000 ppm, more preferably 10 to 5,000 ppm, and even more preferably 20 to 3,000 ppm relative to the total copolymerization components. If the amount is too low, the polymerization reaction tends to be difficult to proceed sufficiently. Even if the amount is too high, there is no advantage in shortening the reaction time and a tendency to cause side reactions.
[0068] The reaction temperature during the esterification reaction is preferably 200-300°C, more preferably 210-280°C, and even more preferably 220-250°C. If the reaction temperature is too low, the reaction tends to be difficult to proceed sufficiently, while if it is too high, side reactions such as decomposition tend to occur. The reaction pressure is usually atmospheric pressure.
[0069] After the above esterification reaction, a polycondensation reaction is carried out. As reaction conditions for the polycondensation reaction, it is preferred to further incorporate the same catalyst as used in the above-mentioned esterification reaction in an amount comparable to that used in the reaction. The reaction temperature is preferably 220 to 280°C, particularly preferably 230 to 270°C, and the reaction system is gradually depressurized to a final pressure of 5 hPa or less. If the reaction temperature is too low, the reaction tends to be difficult to fully proceed, while if it is too high, side reactions such as decomposition tend to occur.
[0070] The resin composition ratio (ratio of structural units derived from each component) of the polyester resin (A) can be determined by, for example, NMR.
[0071] In one embodiment of the present invention, the polyester resin (A) is preferably a polyester emulsion. In addition, "emulsion" refers to resin particles dispersed in an aqueous medium using an emulsifier or a surfactant.
[0072] In one embodiment of the present invention, the polyester resin (A) is preferably a self-emulsifiable resin. If the self-emulsifiable resin is a self-emulsifiable resin, an emulsion can be formed without using an emulsifier or surfactant, thereby obtaining a decorative film with excellent water resistance. In addition, "self-emulsifiable" means that certain hydrophilic groups are introduced into the resin skeleton by chemical means, and the resin itself has emulsification ability without the need to add emulsifiers or surfactants.
[0073] Furthermore, in one embodiment of the present invention, in order to facilitate the water solubility or water dispersion of the polyester resin, the polyester emulsion is preferably at least one emulsion selected from an emulsion obtained by dispersing a polyester resin having a sulfonic acid group in an aqueous medium, and an emulsion obtained by neutralizing a polyester resin having a carboxyl group with an alkaline compound and dispersing it in an aqueous medium.
[0074] Examples of the monomer having a sulfonic acid group and / or a sulfonic acid metal salt group used as a raw material for the polyester resin having a sulfonic acid group include sulfoisophthalic acid, 5-sulfoisophthalic acid, 4-sulfophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5-(4-sulfophenoxy)isophthalic acid, 5-(sulfopropyloxy)isophthalic acid, sulfopropylmalonic acid, sulfosuccinic acid, 2-sulfobenzoic acid, 3-sulfobenzoic acid, 5-sulfosalicylic acid, and methyl esters of these carboxylic acids, or alkali metal salts, alkaline earth metal salts, and ammonium salts of these sulfonic acids.
[0075] The amount of the monomer having a sulfonic acid group and / or a sulfonic acid metal salt group used is preferably 0.1 to 10% by mass, more preferably 2 to 6% by mass, based on the entire polyester resin (A).
[0076] Examples of the monomer having a carboxylic acid group and / or a carboxylic acid metal salt group used as a raw material for the polyester resin having a carboxyl group include the polycarboxylic acids listed above in the "Polycarboxylic Acids (A1)" column, or alkali metal salts, alkaline earth metal salts, ammonium salts thereof, and the like.
[0077] The amount of the monomer having a carboxylic acid group and / or a carboxylic acid metal salt group used is preferably 0.1 to 10% by mass, more preferably 2 to 6% by mass, based on the entire polyester resin (A).
[0078] The basic compound used to neutralize the polyester resin having a carboxyl group is not particularly limited, and examples thereof include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic amines such as trimethylamine, dimethylaminoethanol, 2-methyl-2-amino-1-propanol, triethylamine, and ammonia. Among them, organic amine compounds are preferred, and tertiary amines such as triethylamine, tributylamine, dimethylethanolamine, and diethylenetriamine are particularly preferred.
[0079] (Physical Properties of Polyester Resin (A)) Hereinafter, the physical properties of the polyester resin (A) will be described in detail. From the perspective of adhesive properties, the glass transition temperature of the polyester resin (A) is preferably -100 to 40°C, more preferably -80 to 20°C, and even more preferably -70 to 5°C. When the glass transition temperature is within this range, the polyester resin exhibits excellent stability and water dispersibility.
[0080] The glass transition temperature (Tg) of the polyester resin (A) is a value measured in accordance with JIS K 7121, and can be specifically measured by the method described in Examples.
[0081] The number average molecular weight (Mn) of the polyester resin (A) is preferably 1,000 to 100,000, more preferably 2,000 to 80,000, and even more preferably 4,000 to 50,000. When the number average molecular weight is within the above range, the polyester resin has excellent solubility and dispersibility in water.
[0082] The weight average molecular weight (Mw) of the polyester resin (A) is preferably 8,000 to 200,000, more preferably 10,000 to 180,000, and even more preferably 20,000 to 150,000. When the weight average molecular weight is within the above range, the polyester resin has excellent solubility and dispersibility in water.
[0083] The number average molecular weight and weight average molecular weight of the polyester resin (A) are values converted to standard polystyrene molecular weights measured by gel permeation chromatography (GPC), and can be specifically measured by the method described in Examples.
[0084] The hydroxyl value of the polyester resin (A) is preferably 1 to 50 mgKOH / g, more preferably 2 to 30 mgKOH / g, even more preferably 3 to 20 mgKOH / g, and particularly preferably 4 to 15 mgKOH / g. When the hydroxyl value is within this range, crosslinking efficiency with the curing agent (B) described below tends to be good.
[0085] The acid value of the polyester resin (A) is preferably 10 mgKOH / g or less, more preferably 5 mgKOH / g or less, and even more preferably 3 mgKOH / g or less. When the acid value is within the above range, the polyester resin (A) is less susceptible to hydrolysis, tends to exhibit excellent wet heat durability, adhesive strength, and wet heat whitening resistance, and tends to be less likely to corrode the metal even when a layer such as metal is attached to one side of the adhesive layer.
[0086] The hydroxyl value and acid value of the polyester resin (A) are determined by neutralization titration based on JIS K 0070-1992.
[0087] Curing agent (B) The adhesive composition may further contain a curing agent (B) in addition to the polyester resin (A). The curing agent (B) is not particularly limited as long as it is a component capable of undergoing a crosslinking reaction with the polyester resin (A). Examples of the curing agent (B) include epoxy curing agents, metal chelate curing agents, and isocyanate curing agents.
[0088] The curing agent (B) may be used alone or in combination of two or more. In the adhesive composition, the content of the curing agent (B) is preferably less than 4 parts by mass, more preferably 0.01 to 3 parts by mass, and even more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the polyester resin (A). This embodiment allows the adhesive layer to have the desired viscoelasticity (storage modulus and loss tangent), resulting in a decorative film exhibiting appropriate adhesive strength. Furthermore, a decorative film can be obtained that exhibits sufficient and appropriate crosslinking structure, high cohesive strength, an excellent balance of adhesive properties, and excellent durability.
[0089] Epoxy Curing Agent Examples of epoxy curing agents include epoxy compounds having two or more epoxy groups per molecule, specifically ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylenediamine, N,N,N',N'-tetraglycidylaminophenylmethane, triglycidyl isocyanurate, m-N,N-diglycidylaminophenylglycidyl ether, N,N-diglycidyltoluidine, and N,N-diglycidylaniline. The number of epoxy groups per molecule of these epoxy compounds is, for example, 2 to 10. One or more epoxy curing agents may be used.
[0090] Metal Chelate Curing Agents Examples of metal chelate curing agents include compounds formed by coordination of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium, such as alkoxides, acetylacetone, and ethyl acetoacetate. Among these, aluminum chelate compounds are preferred. Specific examples include aluminum isopropoxide, aluminum sec-butyrate, ethylaluminum diisopropyl acetoacetate, aluminum trisacetoacetate, and aluminum trisacetylacetonate. The metal chelate curing agents may be used alone or in combination.
[0091] Isocyanate curing agent Examples of the isocyanate curing agent include isocyanate compounds having two or more isocyanate groups in one molecule.
[0092] Examples of diisocyanate compounds having two isocyanate groups per molecule include aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates. Examples of isocyanate compounds having three or more isocyanate groups per molecule include aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates. Examples of isocyanate compounds include multimers (e.g., dimers or trimers, biuret forms, isocyanurate forms), derivatives (e.g., addition reaction products of polyols with two or more diisocyanate molecules), and polymers of the above-mentioned isocyanate compounds having two or more isocyanate groups. The isocyanate curing agents may be used alone or in combination.
[0093] Plasticizer (C) The adhesive composition may further contain a plasticizer (C) in addition to the polyester resin (A).
[0094] As the plasticizer (C), for example, an alkyl ester of an aromatic polycarboxylic acid or an alkyl ester of an aliphatic polycarboxylic acid may be mentioned, and an alkyl ester of an aromatic polycarboxylic acid is preferred.
[0095] The plasticizer (C) may be used alone or in combination of two or more. The content of the plasticizer (C) is preferably 2 to 40 parts by mass, more preferably 3 to 30 parts by mass, and even more preferably 4 to 25 parts by mass per 100 parts by mass of the polyester resin (A). If the content is too high, the adhesive strength tends to decrease due to plasticizer bleeding, while if it is too low, the adhesive strength tends to decrease due to reduced compatibility.
[0096] additive In addition to the above components, the adhesive composition may also contain at least one selected from the group consisting of a resin component other than the polyester resin (A), an antistatic agent, a silane coupling agent, an ultraviolet absorber, an antioxidant, a defoaming agent, a filler, a stabilizer, a softener, a viscosity imparting agent, and a wettability modifier, within the scope of not impairing the effects of the present invention.
[0097] organic solvents The adhesive composition preferably contains an organic solvent in order to adjust its coating properties. Examples of the organic solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenethyl ether, and diphenyl ether; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane.
[0098] One or more organic solvents may be used. The content of the organic solvent in the adhesive composition is preferably 0 to 90% by mass, more preferably 10 to 80% by mass.
[0099] (Method for producing adhesive composition) The adhesive composition can be produced by mixing the above-mentioned components sequentially or simultaneously by a known method. Specifically, the adhesive composition can be prepared by mixing the polyester resin (A) and, if necessary, other components such as a curing agent (B), a plasticizer (C), additives, and an organic solvent using a conventionally known method. In one embodiment, for example, the curing agent (B), plasticizer (C), and additives can be added, if necessary, to a polymer solution containing the polyester resin (A) and an organic solvent obtained during the synthesis of the polyester resin (A).
[0100] <Release Film> The decorative film according to one embodiment of the present invention may, if desired, have a release film on the adhesive layer. The release film protects the adhesive surface before the decorative film is actually used and is removed when the decorative film is used. The release film is not particularly limited as long as it facilitates release from the adhesive layer. Examples include resin films, specifically films of polyesters such as polyethylene terephthalate and polybutylene terephthalate; and films of polyolefins such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymer. At least one side of the release film may be treated to facilitate release using a release treatment agent such as a silicone, fluorine-based, long-chain alkyl, or fatty acid amide-based release agent.
[0101] The thickness of the release film is preferably 10 to 500 μm, more preferably 25 to 200 μm.
[0102] <Decorative layer> The decorative film of one embodiment of the present invention may further include a decorative layer between the substrate and the adhesive layer or on the substrate. The decorative layer is provided to impart design to the decorative film and is a layer for displaying patterns, text, or designs.
[0103] <Method for Manufacturing Decorative Film> In producing the decorative film according to one embodiment of the present invention, any method capable of forming a decorative film having a substrate and an adhesive layer can be employed without particular limitation. Examples include a method in which an adhesive composition is applied to a substrate and dried to form an adhesive layer; a method in which a release film is attached to the adhesive layer of the decorative film obtained by this method, as needed; and a method in which an adhesive composition is applied to a release film and dried to form an adhesive layer, and the exposed surface of the resulting adhesive layer not in contact with the release film is attached to a substrate and cured.
[0104] The adhesive layer can be obtained by applying the adhesive composition described above onto a substrate or a release film and drying it. Drying conditions vary depending on the type of organic solvent contained in the composition, the thickness of the adhesive layer, etc., but are generally performed at a temperature of 50 to 150°C and for a time of 1 to 10 minutes.
[0105] Examples of a method for applying the adhesive composition include spin coating, knife coating, roll coating, bar coating, doctor blade coating, die coating and gravure coating.
[0106] Curing conditions are as follows, for example. Curing is preferably performed at 5 to 60°C, more preferably 15 to 50°C, and preferably at 30 to 70% RH, more preferably at 40 to 70% RH, for at least one day, more preferably 2 to 10 days. When crosslinking is performed under these curing conditions, a crosslinked product (network polymer) composed of the polyester resin (A) and the curing agent (B) can be efficiently formed.
[0107] <Applications and Decorative Molded Articles> The decorative molded body having the decorative film according to one embodiment of the present invention is a decorated molded body obtained by attaching the decorative film according to one embodiment of the present invention to at least a portion of the surface of a molded body serving as an adherend.
[0108] Examples of adherends for the decorative film according to one embodiment of the present invention include shaped articles having three-dimensional shapes, preferably articles having three-dimensional curved surfaces. Specifically, examples include vehicle bodies, vehicle interior materials, building materials, and vanity panels. Examples of "vehicles" include four-wheeled vehicles such as passenger cars, buses, and trucks; two-wheeled vehicles such as motorcycles, scooters, and mopeds; and trains.
[0109] The material forming the adherend is not particularly limited, and examples thereof include metal materials; wood; and plastics such as ABS resin, polycarbonate resin, polyester resin, polypropylene resin, and polyethylene resin, and the surface thereof may be painted.
[0110] Examples of methods for attaching the decorative film to the adherend include manual attachment, vacuum forming, compressed air forming, vacuum compressed air forming, and hot high-pressure forming. Among these, vacuum compressed air forming is preferred.
[0111] The decorative molded article comprises a molded article (the adherend) and a substrate with an adhesive layer, wherein the adhesive layer is formed by applying the adhesive layer to the surface of the molded article and removing a release film from the decorative film. More specifically, the decorative molded article comprises, in this order, a molded article, an adhesive layer, a decorative layer (if applicable), and a substrate. Example
[0112] The present invention will be described in more detail below based on Examples, but the present invention is not limited to these Examples. In the following Examples, "parts" means "parts by mass" unless otherwise specified.
[0113] The following physical property values are values measured by the following methods. [Number average molecular weight (Mn)] The number average molecular weight (Mn) in terms of standard polystyrene was determined by gel permeation chromatography (GPC) under the following conditions. ·Measuring device: HLC-8220GPC (manufactured by Tosoh Corporation) GPC column configuration: The following five columns (all manufactured by Tosoh Corporation) (1)TSK-GEL HXL-H (guard column) (2)TSK-GEL G7000HXL (3)TSK-GEL GMHXL (4)TSK-GEL GMHXL (5)TSK-GEL G2500HXL Sample concentration: Dilute with tetrahydrofuran to a concentration of 1.0 mg / cm 3 Mobile phase solvent: tetrahydrofuran Flow rate: 1.0cm 3 / minute Column temperature: 40°C
[0114] [Glass transition temperature (Tg)] The measurement was performed in accordance with JIS K 7121 using a differential scanning calorimeter (manufactured by TA Instruments Co., Ltd., product name: "DSC Q2000") at a heating rate of 20°C / min.
[0115] [Acid value, hydroxyl value] The measurement was conducted in accordance with JIS K 0070-1992.
[0116] <Polyester resin> As the polyester resin constituting the adhesive layer, commercially available products and synthetic products shown in Table 1 below were used. Table 1 shows the physical properties of each polyester resin.
[0117] [Table 1]
[0118] Polyester A: Polyester resin (A-1) described in Japanese Patent Application Laid-Open No. 2022-153321
[0134] Polyester B: Polyester resin (A-3) described in Japanese Patent Application Laid-Open No. 2022-111238
[0129]
[0119] <Preparation of Adhesive Composition> Adhesive compositions were prepared according to the following formulations 1 to 10, and the blending ratios are shown in Table 2. The resulting compositions were described in the form of emulsions and solvent-based compositions.
[0120] [Formula 1-2] In Formulation 1, 25 parts by mass of diethyl phthalate (DEP) as a plasticizer and 2 parts by mass of M-12AT (Soken Chemical Co., Ltd.), an aluminum chelate curing agent, were added to a polyester resin "VYLONAL MD-1480 (manufactured by Toyobo Co., Ltd.)" (solids concentration 25%, based on 100 parts by mass of the solids), and the mixture was stirred and mixed to obtain an adhesive composition (I). In Formulation 2, an adhesive composition (II) was obtained by the same method as in Formulation 1, except that the aluminum chelate curing agent was not added.
[0121] [Recipe 3] A polyester resin "VYLONAL MD-1335 (manufactured by Toyobo Co., Ltd.)" (solid content concentration 30%, containing 30% by mass of isopropyl alcohol (IPA)) was used to obtain an adhesive composition (III).
[0122] [Formula 4-5] To a polyester resin "VYLON 550 (manufactured by Toyobo Co., Ltd.)" (solid content concentration 100%) diluted with methyl ethyl ketone (100 parts by mass in terms of solid content), each component was added in the amount shown in Table 2 to obtain adhesive compositions (IV) and (V).
[0123] [Formula 6-7] In Formulation 6, the components were added in the amounts shown in Table 2 to the polyester A listed in Table 1 (solids concentration 50%, 100 parts by mass based on solids) to obtain an adhesive composition (VI). In Formulation 7, an adhesive composition (VII) was obtained by the same method as in Formulation 6, except that the polyester B listed in Table 1 was used.
[0124] [Formula 8-10] In Formulation 8, the acrylic resin "E03H (manufactured by Soken Chemical Co., Ltd.)" (100 parts by mass in terms of solid content) was used to obtain an adhesive composition (VIII). In Formulations 9 and 10, the acrylic resins "1604N (manufactured by Soken Chemical Co., Ltd.)" and "2094 (manufactured by Soken Chemical Co., Ltd.)" were used, respectively. The components were added in the amounts shown in Table 2 relative to 100 parts by mass of each acrylic resin (in terms of solid content), thereby obtaining adhesive compositions (IX) and (X).
[0125] [Table 2]
[0126] [Example 1] <Production of Decorative Film> The degassed PSA composition (I) was applied to a release-treated polyethylene terephthalate (release film) using a doctor blade and dried at 80°C for 5 minutes to obtain a sheet having a 20 μm-thick coating. A 50 μm-thick, easily moldable polyethylene terephthalate (PET) film "FT50" (manufactured by Teijin Limited) was attached to the coated surface of the sheet and allowed to mature at 23°C / 50% RH for 24 hours to obtain a decorative film comprising the release film, a 20 μm-thick PSA layer, and the easily moldable PET film.
[0127] <Evaluation of physical properties> The physical properties of the decorative film were evaluated as follows. The evaluation results are shown in Table 3. [Preparation of viscoelastic samples] The adhesive layer for viscoelasticity evaluation was prepared using the following procedure. First, a 25 μm thick adhesive layer formed on a release film was laminated onto a 25 μm thick adhesive layer formed on another release film under a 23°C / 50% RH environment. The layer was then autoclaved at 50°C / 5 atm for 20 minutes to produce a 50 μm thick adhesive layer. One release film was peeled off, and the 25 μm thick adhesive layer formed on the other release film was laminated. This process was repeated to produce a viscoelasticity specimen with a total thickness of 1.0 mm.
[0128] [Storage modulus (G')] The viscoelastic spectrum of the viscoelastic specimen having a thickness of 1.0 mm was measured using a "Physica MCR300" manufactured by Anton Paar, using the dynamic viscoelasticity measurement method in accordance with JIS K7244 (temperature range -40 to 180°C, heating rate 3.67°C / min, frequency 1 Hz), and the storage modulus (G') at a temperature of 23°C was measured.
[0129] [Loss tangent (tanδ)] For the above-mentioned viscoelastic sample having a thickness of 1.0 mm, a viscoelastic spectrum was measured using the "Physica MCR300" manufactured by Anton Paar using the dynamic viscoelasticity measurement method in accordance with JIS K7244 (temperature range -40 to 180°C, heating rate 3.67°C / min, frequency 0.01 Hz), and the loss tangent value (tan δ) at a temperature of 23°C was measured.
[0130] [Adhesion strength to polycarbonate (PC) (N / 20mm)] The deaerated adhesive composition (I) was applied with a scraper to a 50 μm thick easy-to-form polyethylene terephthalate (PET) film and dried at 80°C for 3 minutes to form an adhesive layer with a dry film thickness of 20 μm to form an adhesive sheet for an adhesion test. A 150 mm × 20 mm test piece was then cut out of the adhesive sheet and the adhesive layer was attached to a polycarbonate plate adherend. After being placed under a 23°C, 50% RH environment for 30 seconds, the 180-degree peel strength (N / 20 mm) at a peel speed of 300 mm / min was measured using an Autograph to obtain adhesion (a). The adhesion (b) after 20 minutes and the adhesion (c) after 24 hours were obtained under the same conditions as for the adhesion (a), except for changing the placement time after being attached to the adherend. An Autograph ("Autograph AG-X" manufactured by Shimadzu Corporation) was used in the determination of adhesion.
[0131] [Adhesion strength to acrylonitrile butadiene styrene (ABS) (N / 20mm)] The adhesive strength (d) after 30 seconds, the adhesive strength (e) after 20 minutes, and the adhesive strength (f) after 24 hours were determined by the same method as described in the above-mentioned [Adhesion Strength to Polycarbonate (PC) (N / 20mm)], except that the adherend was changed to ABS.
[0132] [Water resistance] The PSA sheet with the easily moldable PET film obtained by the method described in [Adhesion Strength to Polycarbonate (PC) (N / 20 mm)] was immersed in water at room temperature, and changes in appearance after 24 hours were visually evaluated. ○···Transparent △···translucent ×···white turbidity
[0133] [Examples 2 to 5, Comparative Examples 1 to 5] Decorative films of Examples 2 to 5 and Comparative Examples 1 to 5 were prepared in the same manner as in Example 1, except that adhesive compositions (II) to (V) and adhesive compositions (VI) to (X) prepared according to the above-mentioned formulations 2 to 5 and 6 to 10 were used instead of adhesive composition (I). The physical properties of each decorative film were evaluated under the same conditions as those described in the "Evaluation of Physical Properties" column in Example 1. The evaluation results are shown in Table 3.
[0134] [Table 3]
[0135] acrylic resin E03H (manufactured by Soken Chemical Co., Ltd.) 1604N (manufactured by Soken Chemical Co., Ltd.) 2094 (made by Soken Chemical Co., Ltd.) curing agent M-12AT: Aluminum chelate curing agent (manufactured by Soken Chemical Co., Ltd.) L-45: Isocyanate curing agent (manufactured by Soken Chemical Co., Ltd.) E-AX: Epoxy curing agent (manufactured by Soken Chemical Co., Ltd.).
Claims
1. A decorative film comprising a substrate and an adhesive layer formed from an adhesive composition containing a polyester resin (A), wherein: The ratio (b / a) of the adhesive strength (a) to the adhesive strength (b) of the adhesive layer measured by the following adhesion test is greater than 1.5; The storage modulus (G') of the adhesive layer measured by a dynamic viscoelasticity test at 23°C and 1 Hz is 1.0×10 4 Pa and above 1.0×10 7 Pa below; and The adhesive layer has a loss tangent value (tan δ) of 0.5 or more and 10.0 or less when measured by a dynamic viscoelasticity test at 23° C. and 0.01 Hz; [Adhesion test] Adhesion (a): A 150 mm x 20 mm test piece was cut from an adhesive sheet for adhesion testing consisting of a 20 μm thick adhesive layer and a 50 μm thick easily moldable polyethylene terephthalate sheet located on one side of the adhesive layer. The adhesive layer was affixed to a polycarbonate plate. After standing for 30 seconds at 23°C and 50% RH, the 180-degree peel strength (N / 20 mm) at a peel rate of 300 mm / min was measured using a tensile tester. Adhesion (b): A 150 mm x 20 mm test piece was cut from the adhesive sheet used for the adhesion test. The adhesive layer was attached to a polycarbonate plate. The plate was left in an environment of 23°C and 50% RH for 20 minutes. The 180-degree peel strength (N / 20 mm) at a peel speed of 300 mm / min was then measured using a tensile tester to determine the adhesion.
2. The decorative film according to claim 1, wherein The adhesive force (a) is greater than 0.8 N / 20 mm and is less than or equal to 7.0 N / 20 mm.
3. The decorative film according to claim 1 or 2, wherein: The adhesive composition contains less than 4 parts by mass of the curing agent (B) based on 100 parts by mass of the polyester resin (A).
4. The decorative film according to claim 1 or 2, wherein: The polyester resin (A) is a polyester emulsion.
5. The decorative film according to claim 1 or 2, wherein: The polyester resin (A) is a self-emulsifiable resin.
6. The decorative film according to claim 4, wherein: The polyester emulsion is at least one emulsion selected from an emulsion obtained by dispersing a polyester resin having a sulfonic acid group in an aqueous medium and an emulsion obtained by neutralizing a polyester resin having a carboxyl group with a basic compound and dispersing the same in an aqueous medium.
Citation Information
Patent Citations
Decorative sheet, structure containing decorative sheet, and method for producing the same
JP2017119403A
Polyester-based pressure-sensitive adhesive, pressure-sensitive adhesive sheet for optical members, and polyester-based pressure-sensitive adhesive composition
JP2022111238A
Polyester-based adhesive composition, polyester-based adhesive, adhesive sheet, and optical member with adhesive member layer
JP2022153321A